Estudio serológico para el virus de parainfluenza-3 en el Hato BON en el departamento de Antioquia (1998)
ABSTRACT: In a survey of 418 bovine sera from Blanco Orejinegro (BON) cattle were tested by hemoagglutination inhibition (HI) to Parainfluenza-3 (PI3) virus. The prevalence found for different regions of Antioquia were: San José del Nus (50.83%), Rionegro (86.36%), Santa Elena (52.06%), Hatillo 76.34%. it is necessary to determine the economic impact of PI3 on Antioquia bovine population.